Hyperfine and spin-orbit coupling effects on decay of spin-valley states in a carbon nanotube - Pei, T; Palyi, A; Mergenthaler, M; Ares, N; Mavalankar, A; Warner, J; Briggs, G; Laird, E (American Physical Society, 2017)
The decay of spin-valley states is studied in a suspended carbon nanotube double quantum dot via leakage current in Pauli blockade and via dephasing and decoherence of a qubit. From the magnetic field dependence of the leakage current, hyperfine and spin-orbit contributions to relaxation from blocked to unblocked states are identified and explained quantitatively by means of a simple model. The observed qubit dephasing rate is consistent with the hyperfine coupling strength extracted from this model and inconsistent with dephasing from charge noise. However, the qubit coherence time, although longer than previously achieved, is probably still limited by charge noise in the device.